1986
DOI: 10.1080/02786828608959089
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Growth and the Condensation Coefficient for Water: A Review

Abstract: The transfer of gas phase species to aerosols depends a somewhat modified form is presented. Experimental critically on the condensation (or sticking) coefficient. measurements of aerosol growth are consistent with a Reported values for water on water vary from 0.03 to 1. condensation coefficient of unity but indicate that the Theoretical arguments indicate that the condensation thermal accommodation coefficient may be somewhat coefficient should be near unity for polar species on an smaller. Aerosols grown on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 57 publications
1
70
0
Order By: Relevance
“…The difficulty in accurately measuring σ arises from uncertainties in estimating heat and mass transfer resistances and the interfacial temperature in the presence of latent heat transfer [41][42][43] , since vapour pressure is a strong function of temperature. As a result, experimental estimates even in relatively recent studies (since 1989) are scattered over almost two orders of magnitude (0.01 to 1) 31,34,[44][45][46][47] .…”
Section: Condensation Coefficient Of Watermentioning
confidence: 99%
“…The difficulty in accurately measuring σ arises from uncertainties in estimating heat and mass transfer resistances and the interfacial temperature in the presence of latent heat transfer [41][42][43] , since vapour pressure is a strong function of temperature. As a result, experimental estimates even in relatively recent studies (since 1989) are scattered over almost two orders of magnitude (0.01 to 1) 31,34,[44][45][46][47] .…”
Section: Condensation Coefficient Of Watermentioning
confidence: 99%
“…Mozurkewich, 1986;Shaw and Lamb, 1999;Li et al, 2001;Davidovits et al, 2004;Zientara et al, 2005;Winkler et al, 2004Winkler et al, , 2006Kolb et al, 2010), but the converging view is that it is close to unity (≥0.1) for water surfaces. Several theoretical and experimental techniques are used to study water uptake (Davidovits et al, 2006;Kolb et al, 2010).…”
Section: T Raatikainen Et Al: Activation Kinetics From Measurementsmentioning
confidence: 99%
“…Experimental values of q c that range over three orders of magnitudes, from 0.001-1, have been reported since Rideal (Rideal 1925) conducted the first room temperature experiments in 1925 (Mozurkewich 1986;Marek and Straub 2001;Davidovits et al 2004). More recent experiments, for temperatures between 238 and 298 K, have reduced the range to 0.01-1 (Beloded et al 1989;Hagen et al 1989;Shaw and Lamb 1999;Zagaynov et al 2000;Davidovits et al 2006), and Marek and Straub (2001) suggested that condensation coefficients less than 0.01 indicate contamination of the water surface.…”
Section: Droplet Growth Lawsmentioning
confidence: 99%